2011
DOI: 10.1634/theoncologist.2010-0203
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Nutrition Integration: MUST Screening in Cancer

Abstract: Rationale. Nutritional risk screening should be routine in order to select patients in need of nutrition care; this conduct change has to rely on education. In this project, radiotherapy department health professionals were trained on how to use the Malnutrition Universal Screening Tool (MUST), to foster its integration into cancer outpatient management; we also aimed to identify those more adherent to screening.Methods. Research dieticians (the standard) conducted interactive sessions with all physicians, nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The adequate tool for screening undernutrition should be brief and easy to fill, inexpensive, highly sensitive and have good specificity [25]. MUST (Malnutrition Universal Screening Tool) and NRS-2002 (Nutritional Risk Screening-2002) are considered suitable [28,29,30]; the MNA (Mini Nutritional Assessment) is a suitable tool for nutritional assessment in the senior population [19,23].…”
Section: Resultsmentioning
confidence: 99%
“…The adequate tool for screening undernutrition should be brief and easy to fill, inexpensive, highly sensitive and have good specificity [25]. MUST (Malnutrition Universal Screening Tool) and NRS-2002 (Nutritional Risk Screening-2002) are considered suitable [28,29,30]; the MNA (Mini Nutritional Assessment) is a suitable tool for nutritional assessment in the senior population [19,23].…”
Section: Resultsmentioning
confidence: 99%
“…Tsai et al reported the use of the mini nutritional assessment in predicting the nutritional status of patients with liver cancer. Malnutrition Universal Screening Tool was suggested by Boléo–Tomé et al These methods, often including anthropometric, dietary, and subjective assessment, ensure an accurate and comprehensive evaluation. However, most of them are complex and time‐consuming for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Some programs have focused on how to use a specific assessment tool (e.g., MUST). [ 33 35 ] Other programs cover artificial hydration therapy and general nutrition management in cancer patients. [ 32 34 ] Education effectively increased knowledge and confidence[ 32 34 ] but did not improve compliance with nutritional assessment after the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 34 ] Education effectively increased knowledge and confidence[ 32 34 ] but did not improve compliance with nutritional assessment after the intervention. [ 33 35 ] Heterogeneity in types of interventions or outcomes existed, and the participants' age and background varied among studies.…”
Section: Resultsmentioning
confidence: 99%